2016
DOI: 10.1016/j.jbtep.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Twice the negativity bias and half the positivity offset: Evaluative responses to emotional information in depression

Abstract: Background and Objectives Humans have the dual capacity to assign a slightly pleasant valence to neutral stimuli (the positivity offset) to encourage approach behaviors, as well as to assign a higher negative valence to unpleasant images relative to the positive valence to equally arousing and extreme pleasant images (the negativity bias) to facilitate defensive strategies. We conducted an experimental psychopathology study to examine the extent to which the negativity bias and the positivity offset differ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…From an evolutionary perspective, this activation function enables organisms to explore novel environments, with the ultimate goal to find additional sources of nourishment and protection as well as occasions for mating and reproduction (Cacioppo & Berntson, 1994;Cacioppo & Gardner, 1999). Research has shown that positivity offset (as well as negativity bias) can be generalized across different kinds of stimuli (Norris, Larsen, Crawford, & Cacioppo, 2011), is temporally stable and trait-like consistent (Ito & Cacioppo, 2005), and can be used as a theoretical construct to interpret serotonergic function in healthy and clinical populations (Ashare, Norris, Wileyto, Cacioppo, & Strasser, 2013;Carver, Johnson, & Joormann, 2009;Gollan et al, 2016). During our task, positivity offset may have outweighed negativity bias because of the absence of proximal environmental danger which, in turn, promoted exploration (Ito & Cacioppo, 2005;Schettino, Loeys, Bossi, & Pourtois, 2012;Schettino, Loeys, Delplanque, & Pourtois, 2011;Schettino, Loeys, & Pourtois, 2013).…”
Section: Pleasant Information Is Prioritized In Early Visual Cortexmentioning
confidence: 99%
“…From an evolutionary perspective, this activation function enables organisms to explore novel environments, with the ultimate goal to find additional sources of nourishment and protection as well as occasions for mating and reproduction (Cacioppo & Berntson, 1994;Cacioppo & Gardner, 1999). Research has shown that positivity offset (as well as negativity bias) can be generalized across different kinds of stimuli (Norris, Larsen, Crawford, & Cacioppo, 2011), is temporally stable and trait-like consistent (Ito & Cacioppo, 2005), and can be used as a theoretical construct to interpret serotonergic function in healthy and clinical populations (Ashare, Norris, Wileyto, Cacioppo, & Strasser, 2013;Carver, Johnson, & Joormann, 2009;Gollan et al, 2016). During our task, positivity offset may have outweighed negativity bias because of the absence of proximal environmental danger which, in turn, promoted exploration (Ito & Cacioppo, 2005;Schettino, Loeys, Bossi, & Pourtois, 2012;Schettino, Loeys, Delplanque, & Pourtois, 2011;Schettino, Loeys, & Pourtois, 2013).…”
Section: Pleasant Information Is Prioritized In Early Visual Cortexmentioning
confidence: 99%
“…From an evolutionary perspective, this activation function enables organisms to explore novel environments, with the ultimate goal to find additional sources of nourishment and protection as well as occasions for mating and reproduction (Cacioppo & Berntson, 1994;Cacioppo & Gardner, 1999). Research has shown that positivity offset (as well as negativity bias) can be generalized across different kinds of stimuli (Norris, Larsen, Crawford, & Cacioppo, 2011), is temporally stable and trait-like consistent (Ito & Cacioppo, 2005), and can be used as a theoretical construct to interpret serotonergic function in healthy and clinical populations (Ashare, Norris, Wileyto, Cacioppo, & Strasser, 2013;Carver, Johnson, & Joormann, 2009;Gollan et al, 2016). During our task, positivity offset may have outweighed negativity bias because of the absence of proximal environmental danger which, in turn, promoted exploration (Ito & Cacioppo, 2005;Schettino, Loeys, Bossi, & Pourtois, 2012;Schettino, Loeys, Delplanque, & Pourtois, 2011;Schettino, Loeys, & Pourtois, 2013).…”
Section: Pleasant Information Is Prioritized In Early Visual Cortexmentioning
confidence: 99%
“…Previous studies have shown that, in addition to sex (Hall and Matsumoto, 2004 ), age (Mill et al, 2009 ; Hurley et al, 2014 ) and personality (Hurley et al, 2014 ), depression (Liu et al, 2012 ; Gollan et al, 2015b ; Kerestes et al, 2016 ; Milders et al, 2016 ) can affect one’s performance when recognizing ordinary facial expressions. Depression is one of the most common mental illness (Bocharov et al, 2017 ); the official website of WHO reports that the global prevalence of patients with depression exceeds 300 million.…”
Section: Introductionmentioning
confidence: 99%